DEVELOPMENT OF MEDIA CONGKLAK MATH GAMES FOR SUBMISSION OF MATERIAL MAKING KPK AND FPB CLASS IV IN PRIMARY SCHOOL PENGEMBANGAN MEDIA PERMAINAN CONGKLAK MATEMATIKA UNTUK MENGEFEKTIFKAN PENYAMPAIAN MATERI KPK DAN FPB KELAS IV DI SEKOLAH DASAR - Kabut Amrita Nurhayati; Santhy Hawanti; Sony Irianto (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
Mathematics is one of the core subjects taught in schools. Media is one of the conditions that help students understand the learning material. This research development research approach. The main objec-tive of this study was to develop a mathematical congklak game media. In addition, this study also aims to determine the feasibility media congklak math game, know the game congklak media influence the effective-ness of mathematics instructional time, knowing the teacher's response to media congklak math games, and knowing students' response to media congklak math game. Stages of this research refers to the model of development of the media by Riyana and Susilana (2011: 28). Data were collected using the test and non-test techniques. The test is given in the form of pretest and posttest, while non-test questionnaire. To deter-mine the influence of mathematics congklak game media on the effectiveness of learning time be tested on a limited scale that is in the fourth grade at two elementary-Cilacap District of Kesugihan involving control class and experimental class. The results showed that the media play a decent congklak used for learning math. Other results showed the use of mathematical congklak media can streamline the delivery of material KPK and FPB in class IV. This can be seen from the results of hypothesis testing using Independent sample T-test is ????ℎ????????= 0,002 Sig (2-tailed) and the final is 0,001< α = 0,05.The results showed that Ho is rejected or there is influence between the experimental class and control class. Results of the teacher's response shows teachers strongly agree with the use of mathematical congklak media is evidenced by an average score of 4.7 teacher response. Other results that student responses with an average score of 3.8 showed the students are happy with the learning using mathematical congklak media.